Digital Technologies and Selective Exposure: How Choice and Filter Bubbles Shape News Media Exposure. (October 2019) - Cardenal, Ana S.; Aguilar-Paredes, Carlos; Galais, Carol; Pérez-Montoro, Mario
This paper analyzes the role of different origins to news media in selective exposure. We rely on a unique web-tracking online dataset from Spain to identify points of access to news outlets and study the influence of direct navigation and news-referred platforms (i.e., from Facebook and Google) on selective exposure. We also explore cross-level interactions between origins to news and political interest and ideology. We find that direct navigation increases selective exposure while Google reduces it. We also find that the relationship between origins to news and selective exposure is strongly moderated by ideology, suggesting that search engines and social media are not content neutral. Our findings suggest a rather complex picture regarding selective exposure online.